Booklet Berbasis Augmented Reality melalui Pembelajaran PBL Materi Keseimbangan Ekosistem untuk Meningkatkan Literasi Sains Kelas V SDN Sumberingin 04 Blitar - Sari, Putri Ana; Fatih, Mohamad; Alfi, Cindya (MODELING: Jurnal Program Studi PGMI, 2024)
This study developed an augmented reality (AR)-based booklet media for ecosystem balance material in grade V elementary school. The media was validated by material, media, and language experts and deemed very suitable for use based on teacher assessments. The media trial on students showed a significant increase in science literacy skills, with an N-Gain value of 0.83 (high category). This result indicates that the AR-based booklet media integrated with the Problem Based Learning (PBL) learning model is effective in improving students' science literacy.